(untitled) (Tribhuvan University Journal of Microbiology, 2021)
Objective: Antibiotic toxicity and multi drug resistant pathogens are the two greatest challenges that today’s medical world has been facing. As a consequence of the haphazard use of antimicrobials, the spread of antimicrobial resistance is now a global issue. This study aimed to investigate antimicrobial activity of some common spices. Methods: During the study period Five commonly used spices were collected from local market of Lagankhel, Lalitpur. The antimicrobial activity of selected naturally grown spices was done against two gram positive and three gram-negative pathogenic bacteria. The extracts of the spices were obtained by using absolute ethanol (99.9%) to carry out the antibacterial susceptibility assay using agar well diffusion method. Results: The result of agar well diffusion method showed Clove and Cinnamon were found to possess relatively higher antimicrobial activities by preventing the growth of all 5 tested bacteria. Gram positive bacteria were found to be more sensitive to spices than Gram negative bacteria. Conclusion: The finding of this study showed that extract of spices can be alternative to synthetic drugs to control infectious diseases.